EVALUASI KEBIJAKAN PENGELOLAAN KEUANGAN DI DINAS PENDIDIKAN KABUPATEN KUTAI TIMUR (STUDI DI UPT PENDIDIKAN MUARA BENGKAL) - Aweq Ampung; Adam Idris; Achmad Djumlani (Jurnal Administrative Reform, 2017)
This study has two objectives: first, to know the financial management system in East Kutai District Education Office in particular UPT Bengkal Muara Education and Evaluation and second, to know the policies relating to the management of the Department of Education in East Kutai in particular financial delegation to the Education Unit in Muara Bengkal. In this study the author uses primary data from informants which are structural officials and employees directly involved in the financial management system and other relevant officials.